Recent Approaches to the Identification of Novel Microtubule-Targeting Agents - Eli, Susanna; Castagna, Rossella; Mapelli, Marina; Parisini, Emilio (Frontiers in Molecular Biosciences, 2022)
Microtubules are key components of the eukaryotic cytoskeleton with essential roles in cell division, intercellular transport, cell morphology, motility, and signal transduction. They are composed of protofilaments of heterodimers of a-tubulin and b-tubulin organized as rigid hollow cylinders that can assemble into large and dynamic intracellular structures. Consistent with their involvement in core cellular processes, affecting microtubule assembly results in cytotoxicity and cell death. For these reasons, microtubules are among the most important targets for the therapeutic treatment of several diseases, including cancer. The vast literature related to microtubule stabilizers and destabilizers has been reviewed extensively in recent years. Here we summarize recent experimental and computational approaches for the identification of novel tubulin modulators and delivery strategies. These include orphan small molecules, PROTACs as well as light-sensitive compounds that can be activated with high spatio-temporal accuracy and that represent promising tools for precision-targeted chemotherapy.